Nail changes in tuberous sclerosis: are all of them caused by Koenen fibromas? - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
In this 35-year-old woman suffering from tuberous sclerosis, who had already undergone numerous removals of Koenen fibromas, there are still Koenen tumors evident on the 2nd and 3rd finger of the left foot and on the 3rd and 4th of the right foot. On the second toe of the left foot is clearly seen as fibroma was responsible for a deep longitudinal groove of the nail plate. On the third finger of the left foot there is complete atrophy of the nail plate and recurrence of Koenen tumor after removal of a previous large fibroma. We also note on the big toes thickening of the nail lamina with defect of bending and longitudinal streaks, hyperkeratosis of the cuticle of the left big toe and friable pachyonychia on the 4th left finger. According to some Authors (1) the majority of nail changes in tuberous sclerosis are linked to clinically overt or subclinical Koenen tumors, but some alterations such as friable pachyonychia seem independent of the presence of Koenen tumors.